The life expectancy gap between North and South Korea from 1993 to 2008 - Bahk,J; Ezzati,M; Khang,Y-H (European Journal of Public Health, 2018)
Background: Comparative research on health outcomes in North and South Korea offers a unique opportunity to explore political and social determinants of health. We examined the age- and cause-specific contributions to the life expectancy (LE) gap between the two Koreas. Methods: We calculated the LE at birth in 1993 and 2008 among North and South Koreans, and cause-specific contributions to the LE discrepancy between the two Koreas in 2008. The cause-specific mortality data from South Korea were used as proxies for the cause-specific mortality data in North Korea in 2008. Results: The LE gap between the two Koreas was approximately 1 year in 1993, but grew to approximately 10 years in 2008. This discrepancy was attributable to increased gaps in mortality among children younger than 1 year and adults 55 years of age or older. The major causes of the increased LE gap were circulatory diseases, digestive diseases, infant mortality, external causes, cancers and infectious diseases. Conclusions: This study underscores the urgency of South Korean and international humanitarian aid programs to reduce the mortality rate of the North Korean people.